THE INFLUENCE OF COMPANY SIZE AND CAPITAL STRUCTURE ON COMPANY PROFITABILITY IN PT. TRISAKTI OTTO PRATAMA IN PALEMBANG - Dandi, Dandi; Rahayu, Endang; Aminus, Rahmi (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This study was conducted to analyze the management of company size (firm size) and capital structure (DER) of distributors and also to re-examine the influence of these variables on profitability with quantitative research with descriptive methods, namely by analyzing and describing financial report data to determine the category of company health at PT Trisakti Otto Pratama Palembang for the period 2017 to 2021.